2022
DOI: 10.1177/03635465221080162
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Outcomes After Hip Labral Augmentation in Revision Hip Arthroscopy

Abstract: Background: Labral augmentation has emerged as an essential procedure to address a deficient or irreparable labrum while preserving native labral tissue and restoring the hip suction seal mechanism. Purpose: To evaluate midterm outcomes of arthroscopic hip labral augmentation for labral insufficiency after previous hip arthroscopy. Study Design: Case series; Level of evidence, 4. Methods: Patients were identified from a prospectively collected database who underwent arthroscopic hip labral augmentation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Satisfaction could be measured by a 5-point Likert scale (1=very dissatisfied; 2=dissatisfied; 3=neutral; 4=satisfied; 5=very satisfied), 10-point Likert scale (1=completely unsatisfied; 10=completely satisfied) or a postoperative questionnaire whether the patient would choose the same anaesthetic or analgesia handling by the answer of ‘yes’ or ‘no’. 108 …”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Satisfaction could be measured by a 5-point Likert scale (1=very dissatisfied; 2=dissatisfied; 3=neutral; 4=satisfied; 5=very satisfied), 10-point Likert scale (1=completely unsatisfied; 10=completely satisfied) or a postoperative questionnaire whether the patient would choose the same anaesthetic or analgesia handling by the answer of ‘yes’ or ‘no’. 108 …”
Section: Methods and Analysismentioning
confidence: 99%
“…Open access 2=dissatisfied; 3=neutral; 4=satisfied; 5=very satisfied), 10-point Likert scale (1=completely unsatisfied; 10=completely satisfied) or a postoperative questionnaire whether the patient would choose the same anaesthetic or analgesia handling by the answer of 'yes' or 'no'. 108 Exploratory outcomes 1. Perioperative sensory block: Sensory block was evaluated using a 3-point scale (0=no block, 1=analgesia (patient can feel touch, not cold), 2=anaesthesia (patient cannot feel touch)), which was assessed in the anterior, lateral and medial aspects of the mid-thigh.…”
Section: Patient Satisfactionmentioning
confidence: 99%
“…We can have a comprehensive understanding of students, provide decision support for students, and have self-evident practical significance for further understanding students’ behavior characteristics and decision support of school management. For the convenience of function display and user interaction, the system adopts b\s architecture, and the system structure is shown in Figure 5 ( Soares et al, 2022 ). It mainly includes data layer, processing layer and application layer.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, labral augmentation may be beneficial for articular cartilage protection because of the preservation of the native chondrolabral junction. In addition to the cadaveric research, promising clinical outcomes of labral augmentation using various autografts have been shown in recent clinical studies [15][16][17] . Consistent with the results mentioned above, we found that the synovial fluid concentrations of IL-1b and TNF-a in the AUG group increased from 6 to 12 weeks and then declined at 24 weeks.…”
Section: Chondroprotective Potential Of Labral Augmentationmentioning
confidence: 99%